PENAFSIRAN KAUM ‘AD DALAM AL-QUR’AN STUDI ANALISIS ORIENTALIS DAN I’JAZ GHAIB - Fitriani Asri (AL-FIKRA, 2019)
This thesis was entitled the interpretation of people of ‘Ad in Alquran the Orientalist and I’jaz Ghaibi analysis study. This library research gathered the data from literature treasury and enacted text world, especially tafsir books and books that were related to this research, as primary object of analysis. In this research, the applied approach was Tafsir Maudhu’iy approach, referring to Alquran based on classical and contemporary tafsir. This research applied several steps and requirements in drawing the conclusion based on concrete data. The results showed that the people of ‘Ad were categorized into I’jaz Ghaibi, which explained that there was unseen history and refuted the orientalist claim that considered this history as a fairy tale. Richard Bell stated that in narrating the story that were mentioned in Alquran, Muhammad SAW (blessing of Allah and peace be upon him) used Injil as reference, especially Old Testament. In addition, half of the advocacy stories such as people of ‘Ad and Tsamud were taken from Arab reference. However, most of contents that were used by Muhammad to interpret his teaching were taken from Yahudi Nasrani sources. This history was mentioned in Alquran in order to warn human that whatever power or might that human have, they will be destroyed in world and hereafter if they do not obey Allah and his messengers. In addition, this history aimed to motivate Prophet Muhammad SAW to stand firm in delivering the message that was entrusted to him because only certain people were able to directly receive and change the teaching of the messengers of Allah Swt. Nicholas Clapp, a scientist from France, found out the facts relating to the trace of people of ‘Ad remnant. The people of ‘Ad was extinct because they had no descendant. They were annihilated by Allah through disasters and windstorm. The people of ‘Ad were renowned for their ability to build lofty towers. They built those towers as sign for merchants and travelers who were traveling across the city of Iram.Kata Kunci : People of ‘Ad, the Orientalist, I’jaz Ghaibi.